Sustainable use of wood in wine spirit production - Canas, Sara (2022)
A comprehensive overview of the sustainability of wood-based technologies for the production of high-quality and differentiated wine spirits, and the research carried out in this field is provided in this chapter. Barrels are actively involved in the wine spirit's composition and sensory changes due to the transfer of oxygen, and extractive compounds from wood to the beverage. The key physicochemical phenomena and determining factors at the aging stage are illustrated with regard to the sustainable use of wood both in barrels and through innovative technologies for wine spirit's aging. A broad perspective is offered to readers on the fair and sustainable use and reuse of wood, the circular economy and its relationship with cooperage efficiency, including responsible relations/commitments in the entire value chain (from the forest to the aged wine spirit).